OPTIMIZING SPORT PERFORMANCE IN DOGS - Pellegrino, Francisco Javier (2014)
Canine physical performance depends on genetic, training and nutritional factors. Training and nutrition can be easily modified. Exercise and diet programs must be established in order to maximize performance on a given activity. To evaluate physical condition of dogs and get maximum performance, objective parameters such as the observation of variations in heart rate and determination of blood lactate must be established. The latter has been shown as an appropriate, practical and simple method that contributes to quantify the metabolic response to effort. Nowadays the use of motorized treadmills allows to perform specific training routines and, although further studies are required, its application in canines has a promising place to maximize sports performance.